Glucosylceramide production maintains colon integrity in response to Bacteroides fragilis toxin‐induced colon epithelial cell signaling. Issue 12 (13th October 2020) - Patterson, Logan; Allen, Jawara; Posey, Isabella; Shaw, Jeremy Joseph Porter; Costa‐Pinheiro, Pedro; Walker, Susan J.; Gademsey, Alexis; Wu, Xinqun; Wu, Shaoguang; Zachos, Nicholas C.; Fox, Todd E.; Sears, Cynthia L.; et al.
Abstract: Enterotoxigenic Bacteroides fragilis (ETBF) is a commensal bacterium of great importance to human health due to its ability to induce colitis and cause colon tumor formation in mice through the production of B. fragilis toxin (BFT). The formation of tumors is dependent on a pro‐inflammatory signaling cascade, which begins with the disruption of epithelial barrier integrity through cleavage of E‐cadherin. Here, we show that BFT increases levels of glucosylceramide, a vital intestinal sphingolipid, both in mice and in colon organoids (colonoids) generated from the distal colons of mice. When colonoids are treated with BFT in the presence of an inhibitor of glucosylceramide synthase (GCS), the enzyme responsible for generating glucosylceramide, colonoids become highly permeable, lose structural integrity, and eventually burst, releasing their contents into the extracellular matrix. By increasing glucosylceramide levels in colonoids via an inhibitor of glucocerebrosidase (GBA, the enzyme that degrades glucosylceramide), colonoid permeability was reduced, and bursting was significantly decreased. In the presence of BFT, pharmacological inhibition of GCS caused levels of tight junction protein 1 (TJP1) to decrease. However, when GBA was inhibited, TJP1 levels remained stable, suggesting that BFT‐induced production of glucosylceramide helps to stabilize tight junctions. Taken together, our data demonstrate a glucosylceramide‐dependent mechanism by which the colon epithelium responds to BFT.